2020
DOI: 10.3389/fcvm.2020.610282
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and LDLR Are Upregulated in Hearts of Sudden Cardiac Death Victims With Heart Failure With Preserved Ejection Fraction and Diabetes Mellitus

Abstract: Background: Diabetes mellitus (DM) is associated with increased risk of sudden cardiac death (SCD), particularly in patients with heart failure with preserved ejection fraction (HFpEF). However, there are no known biomarkers in the population with DM and HFpEF to predict SCD risk.Objectives: This study was designed to test the hypothesis that osteopontin (OPN) and some proteins previously correlated with OPN, low-density lipoprotein receptor (LDLR), dynamin 2 (DNM2), fibronectin-1 (FN1), and 2-oxoglutarate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The vital roles of FN1 and POSTN in heart and kidney disease have previously been reported. discovered that the expression of FN1 increased in patients with sudden cardio death [46]. Cardiofibrosis has a significant influence on the prognosis of heart diseases, which can be regulated by POSTN [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vital roles of FN1 and POSTN in heart and kidney disease have previously been reported. discovered that the expression of FN1 increased in patients with sudden cardio death [46]. Cardiofibrosis has a significant influence on the prognosis of heart diseases, which can be regulated by POSTN [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The vital roles of FN1 and POSTN in heart and kidney disease have previously been reported. Wang et al found that FN1 was associated with immune infiltration in diabetic nephropathy [ 43 ], Su et al reported that FN1 could regulate the process of renal fibrosis [ 44 ], Zhao et al disclosed that FN1 was involved in rat H9C2 cardiomyocyte growth by regulating cell cycle arrest [ 45 ], and Patel et al discovered that the expression of FN1 increased in patients with sudden cardio death [ 46 ]. Cardiofibrosis has a significant influence on the prognosis of heart diseases, which can be regulated by POSTN [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In people with SCD, type 2 diabetes mellitus, and preserved ejection fraction, the expression of the FN1 gene (fibronectin 1) is higher than in those who died from other causes. The FN1 gene is known to be a candidate gene for IHD [48].…”
Section: Dna Methylation and Ischemic Heart Diseasementioning
confidence: 99%
“…Troponin subunit [33] PLA2G7 -phospholipase A2 group VII; 6p12.3 Degradation of platelet activating factor [35] MMP9 -matrix metallopeptidase 9; 20q13.12 Degradation of collagen of IV and V types Hypomethylation of the gene promoter is associated with IHD, higher levels of PTX3 protein in the blood plasma [28] The level of PTX3 protein in the blood plasma is higher in the group with fatal ACS related to coronary thrombosis as compared with the control group [29] as well as in persons with advanced endpoints (including cardiac death) related to the chronic heart failure [30] MMP9 -matrix metallopeptidase 9; 20q13.12 Gene methylation is associated with the risk of IHD, age when it started developing, IHD risk factors [24] The level of MMP-9 in the blood plasma is considered as a risk marker for SCD [39] FN1 -fibronectin 1; 2q35 Gene promoter hypermethylation is associated with IHD [47] Gene expression is higher in people with SCD, type 2 diabetes mellitus, and preserved left ventricular ejection fraction as compared with persons who died from another cause [48] F2RL3 -F2R like thrombin or trypsin receptor 3; 19p13.11 Gene methylation is associated with cardiovascular mortality in case of IHD [50] ABCB1 -ATP binding cassette subfamily B member 1; 7q21.12 Gene promoter methylation is associated with the risk of ischemic events (including cardiac death, myocardial infarction, ischemic stroke) in case of intracranial stenosis [52] FOXP3 -forkhead box P3; Xp11.23 Gene hypermethylation is associated with IHD [17]…”
Section: Gck -Glucokinase; 7p13mentioning
confidence: 99%
“…Low density lipoprotein (LDL) receptor (Ldlr) plays a key role in the regulation of cholesterol metabolism by removing excess low density lipoprotein cholesterol from the circulation [72]. However, in pathological conditions, a high expression level of Ldlr is a risk factor [73,74]. Oxidized LDL and its receptor Olr1 may play a role in a proinflammatory phenotype in pulmonary arterial hypertension [75].…”
Section: Comparison Of Degs Between Moderate and High-intensity Exercisementioning
confidence: 99%